Faktor-faktor yang Mempengaruhi Risiko Produksi Usahatani Padi Sawah Tadah Hujan (Studi Kasus di Kelurahan Soreang Kecamatan Lau Kabupaten Maros) - Syamsul Anugrah Alamsyah; Arifin Arifin; Mohammad Anwar Sadat (Jurnal Agribis, 2021)
Production risk of rainfed lowland rice farming is focused on climate change which is faced with the problem of flooding during the rainy season and drought in the dry season as well as a very long planting season so that production is expected not only to be able to meet household needs but also for commercialization. carried out in Soreang Village, Lau Subdistrict, Maros Regency, where this research was conducted from January to March 2021, the data method used was multiple regression analysis and the results of this study were that land area, seeds, and fertilizers had a significant effect on production.